Exploring Public Perceptions of Urban Resilient Design: Insights from Mental Mapping - Yuan, Shuai; Maliki, Nor Zarifah (International Journal of Property Sciences (E-ISSN: 2229-8568), 2025)
Urban resilient design is a crucial strategy in urban sustainable development, which needs to be understood by the public. However, misunderstandings surrounding resilient design often impede its effective implementation and impact. This study explores public perceptions of urban resilient design characteristics and the factors influencing such perceptions. Through interviews and mental mapping of 14 participants between the ages of 18 and 65, the study was analysed based on landscape perception theory, combined with mental mapping and field interviews. Our findings reveal personalised painting mechanisms influenced by subjective factors and explore participants’ experiences and feelings in depicting natural and built elements, as well as route reviews. The results highlight how participants’ perception of resilient design manifested itself in the routes and key elements they described, with subjective factors such as age, identity and familiarity playing a key role. Moreover, the study describes how experience shapes public perceptions of robustness, adaptability, redundancy, efficiency, and connectivity, while familiarity influences perceptions of diversity and modularity. Based on these insights, the study proposes strategies to optimise resilient design characteristics, which have important implications for promoting sustainable urban development.